How accurate is translaryngeal ultrasound when compared to flexible nasal endoscopy in viewing vocal cord mobility in children? - Ramyead, Divya Pallavi (Division of General Surgery, 2026)
Objectives: Flexible fibreoptic laryngoscopy (FFL) is currently the gold standard for assessment of true vocal cord (TVC) mobility but is invasive and not without risk. The COVID-19 pandemic has led to growing interest in assessment tools that avoid aerosol generation and risk for transmission of disease. Transcutaneous laryngeal ultrasonography (TLUS) is a potentially useful, non-invasive alternative diagnostic tool for assessing true vocal cord (TVC) mobility.The aim was to determine the accuracy of an application-based TLUS as a screening tool for mobility of the true vocal cords (TVC), and to assess the feasibility of its use by an otolaryngologist not formally trained in ultrasonography. Methods: This was a prospective cohort study conducted after approval by human research ethics committee (HREC 202/2021). Forty children attending the ENT clinic at Red Cross War Memorial Children's Hospital (RCWMCH) for an upper airway assessment with FFL were recruited. Exclusion criteria were children on oxygen; with airway instability, and with behavioural disorders. The first author (DR), an ENT registrar without prior knowledge of ultrasonography, was trained by a consultant radiologist to use the Lumify® handheld ultrasound probe and application tool to assess the larynx and true vocal cord mobility. Combined TLUS and FFLs, short, looped and anonymised videos were formulated. Two qualified ENT specialists (neither trained in ultrasonography) consented to evaluate videos for true vocal cord mobility. Results: In total, 135 videos were obtained from 40 participants. Ages ranged from10 days to 9 years, and the genders were equally represented. On FFL, 92.5% (n=37/40) had normal TVC mobility and 7.5% (n=3/40) had unilateral TVC palsy. The overall accuracy of TLUS evaluation was 95.5% (sensitivity of 100%, specificity of 60%). Although the proportion of cases where normal mobility was correctly identified was 93.3% (n=120/135), the proportion of cases in which abnormal mobility (unilateral vocal cord mobility) was present and correctly identified was 100% (n=135/135). The reliability of TLUS when compared to FFL showed a p value <0.001 and a 100% agreement between ENT specialists evaluating the shared videos. Conclusions: Our study shows TLUS to be a reliable method of assessing TVC mobility. It is also portable, non–invasive and easy-to-use, making it a potentially useful screening tool especially in resource-limited settings, where FFL might not be readily available. Furthermore, it has potential benefit as a screening tool for TVC assessment for practitioners other than radiologists, e.g., otolaryngologists, who have a good understanding of laryngeal anatomy. More studies are needed to fully elucidate use of diagnostic and therapeutic ultrasound in children with airway conditions.